KUALITAS PELAYANAN ADMINISTRASI DAN KEPUASAN MASYARAKAT DI PUSKESMAS SOPAAAH KABUPATEN PAMEKASAN - Eka Yulianti; Dwi Astutiek (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe community assessment of administrative service performance at Puskesmas Sopaaah, Pademawu District, Pamekasan Regency. This research used a qualitative descriptive approach with data collection techniques through in-depth interviews, observation, and documentation. The informants consisted of service users, administrative staff, and the head of the health center. The results showed that community assessments of administrative services were varied. The community assessed that service speed was still slow, procedures were convoluted, staff attitudes were less responsive, waiting room facilities were inadequate, and information dissemination was still suboptimal. The main obstacles faced were limited staff, manual information systems, and budget constraints. This study recommends increasing staff, service digitization, facility improvement, strengthening socialization, and enhancing staff competency to improve the quality of administrative services at Puskesmas Sopaaah.